Association of prenatal trajectories of depressive and anxiety symptoms with neurodevelopment of children aged 0-24 months: A prospective study - Chen, Ruoqing; Liu, Weiying; Wu, Feng; Ye, Xiaomin; Wang, Xuanshu; Zheng, Yeqi; Tan, Weiri; Ding, Ruyi; Liu, Mengting; Gao, Yi; Liang, Hui; Zhang, Quanfu; et al. (Frontiers in Psychiatry, 2025)
BackgroundPrenatal depression and anxiety can significantly impact a child’s neurodevelopment. However, the specific timing and patterns of these maternal psychological symptoms during pregnancy that influence the child’s neurodevelopment remain unclear. This study aimed to investigate the associations of maternal depressive and anxiety symptoms across pregnancy trimesters and their trajectories with neurodevelopmental outcomes in children aged 0 to 24 months.MethodsA total of 16,229 singletons born between January 2020 and December 2023 were included in this prospective study. Maternal depressive and anxiety symptoms in each trimester of pregnancy were assessed by Patient Health Questionnaire-9 and Generalized Anxiety Disorder-7 scale, respectively. The neurodevelopmental status of children aged 0-24 months was assessed by the Ages and Stages Questionnaire-Third Edition. Group-based trajectory model was employed to identify distinct trajectories of prenatal depressive and anxiety symptoms throughout pregnancy. Poisson regression was used to assess the associations of maternal depressive and anxiety symptoms, as well as their trajectories, with the child’s neurodevelopment.ResultsA total of 1,791 (11.04%) children had neurodevelopmental delay in the communication domain, 1,127 (6.94%) in the gross motor domain, 1,750 (10.78%) in the fine motor domain, 1,137 (7.01%) in the problem-solving domain, and 1,724 (10.62%) in the personal-social domain. Maternal depressive and anxiety symptoms during pregnancy, especially in the second and third trimester, were associated with a higher risk of neurodevelopmental delay in all domains, with the most profound impact observed in the fine motor domain. Four trajectories were identified for prenatal depressive and anxiety symptoms, respectively. Compared with children whose mothers had low level of depressive or anxiety symptoms throughout pregnancy, children whose mothers experienced consistently moderate or high level of these symptoms had a higher risk of neurodevelopmental delay, while children whose mothers experienced moderate level of depressive or anxiety symptoms that decreased to low levels after the first trimester did not show a different risk of neurodevelopmental delay.ConclusionMaternal depressive and anxiety symptoms during pregnancy have an adverse impact on the neurodevelopment in offspring. This study highlights the importance of improving the mental health of pregnant women in order to support optimal neurodevelopment for their children.